Changing the Cortical Conductor’s Tempo: Neuromodulation of the Claustrum - Wong, Kelly L. L.; Nair, Aditya; Augustine, George J. (Frontiers in Neural Circuits, 2021)
The claustrum is a thin sheet of neurons that is densely connected to many cortical regions and has been implicated in numerous high-order brain functions. Such brain functions arise from brain states that are influenced by neuromodulatory pathways from the cholinergic basal forebrain, dopaminergic nuclei, and serotonergic raphe. Recent revelations that the claustrum receives dense input from these structures have inspired investigation of state-dependent control of the claustrum. Here, we review neuromodulation in the claustrum – from anatomical connectivity to behavioral manipulations – to inform future analyses of claustral function.